Social determinants that condition early sexual activity of adolescents - Fernández Tapia, Sonia Benita (2020)
Objective. To analyze the social determinants that condition early sexual activity of adolescents. Methods. Quantitative, descriptive, explanatory and cross-sectional study. The sample comprised 254 students between 14 and 18 years of age. A questionnaire was applied to them. It evaluated the personal, family and contextual dimensions and the initiation of sexual activity. For the analysis of the relationship between variables, chi-square statistical test and multiple linear regression model were used. Results. Personal conditioning factors, age of sexual initiation, lack of contraceptive use, and little knowledge of the signs and symptoms of sexually transmitted infections were identified. Among determinants related to their families, level of education of their parents, support from their mothers, and verbal and physical violence appear to have a significant association. Along with the lack of habit of going to health services, television programs and friends appear as the ones that most promote the initiation of early sexual activity. Conclusions. Personal, family and contextual are determinants that significantly influence initiation of adolescent sexual activity, affecting their sexual and reproductive health.